Routine clinical motion analysis: comparison of a bespoke real-time protocol to current clinical methods. Issue 2 (25th January 2019) - Millar, Lindsay Jane; Meng, Lin; Rowe, Philip John
Abstract: Motion analysis (MA) hardware has recently become more accessible; however, protocols have not developed in conjunction. Routine clinical assessment mostly relies on unreliable observational methods. This study aimed to develop an MA protocol for routine clinical use and compare kinematics and reliability to the gold-standard. Ten participants completed 10 over ground walks with a comprehensive marker set (bespoke and gold-standard). Inter/intra-assessor reliability was also compared. Results demonstrated comparable kinematics. Reliability of the bespoke model was lower than the gold standard but higher than observational methods. The bespoke model can be recommended for routine clinical use to assess patient progress and function.